Sanksi Pidana Akibat Pembunuhan Terhadap Istri Di Pengadilan Negeri Kelas I A Padang - Tresia Elda (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2016)
Abstract:Criminal act of murder that occurred in the household has special properties and special sanction. The specialty of this action lies in the relationship between the perpetrator and the victim. In cases of criminal acts other actors sometimes do not know the victim at all and often do not have a relationship. But the crime of murder in the household perpetrators and victims have a special relationship that is related by blood (parent, child, nephew), for example working relationship bonding housemaid and living in a house with actors and marital relationships (husband and wife). Final recent criminal acts of domestic homicide in the city of Padang increased especially that caused the death of the victim conducted by the husband that caused by some factors such us economy and other factors.Keywords: Murder, Victim and Household. Abstrak:Tindak pidana pembunuhan yang terjadi di dalam rumah tangga memiliki sifat khusus dan sanksi khusus. Kekhususan tersebut terletak pada hubungan antara pelaku dan korban. Dalam kasus tindak pidana yang tidak ada hubungan suami isteri terkadang tidak mengenal korban sama sekali. Namun tindak pidana pembunuhan dalam rumah tangga, pelaku dan korban memiliki hubungan khusus atau hubungan darah (orang tua, anak, keponakan) atau bisa juga ikatan kerja sebagai pembantu rumah tangga dan hubungan perkawinan (suami istri). Dalam beberapa waktu terakhir, kasus pembunuhan dalam rumah tangga mengalami peningkatan secara jumlah di kota Padang yang dilakukan oleh suami yang disebabkan beberapa faktor seperti faktor ekonomi dan lainnya.Kata Kunci: Pembunuhan, Korban dan Rumah Tangga.